2021
DOI: 10.1192/j.eurpsy.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and cardiometabolic risk in severe mental disorders: The mediating role of cognitive control

Abstract: Background Cardiometabolic risk is increased in severe mental disorders (SMDs), and there appears to be a relationship between childhood trauma and cardiometabolic risk, possibly related to adverse health behavior. The current study examined the association between childhood trauma and serum lipids and adiposity in SMDs and the potential mediating role of cognitive and personality characteristics. Methods Participants with schizophrenia and bipolar spectrum disorders (N = 819) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…14,17,18,[22][23][24][25]29 . Twelve studies 11,12,13,[15][16][17][19][20][21]25,26,29 showed a significant association between ACE and obesity, with four studies 13,17,25,29 reporting an association between parental loss or separation and obesity, while other studies reported that SA 17,19,22,8,9,23 and PA 15 were associated with obesity.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…14,17,18,[22][23][24][25]29 . Twelve studies 11,12,13,[15][16][17][19][20][21]25,26,29 showed a significant association between ACE and obesity, with four studies 13,17,25,29 reporting an association between parental loss or separation and obesity, while other studies reported that SA 17,19,22,8,9,23 and PA 15 were associated with obesity.…”
Section: Resultsmentioning
confidence: 98%
“…846 were excluded at the title and abstract level and 62 studies that met the inclusion criteria were retrieved and assessed at full text level. Twenty articles 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Figure 1) published between 2011 and 2021 met the criteria for our final review. The majority of these studies (n = 12) were cross-sectional, 14,[17][18][21][22][23][24][25][26][27][28][29] while seven were case-control studies, 1,11,13,15,16,19,20 and one study was prospective, monitoring the weight gain in the participants for a year.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic stress, particularly childhood trauma, has detrimental consequences that lead to metabolic syndrome [320] and schizophrenia [321], which has been proven in the genetic changes of persons with metabolic syndrome [322] and persons with schizophrenia [203]. These interactions are also illustrated through the association between childhood trauma and metabolic syndrome in persons with schizophrenia [137,323]. Recent findings postulate that schizophrenia risk loci can influence stochastic variation in gene expression through epigenetic processes, highlighting the intricate interaction between the genetic and epigenetic control of neurodevelopmental trajectories, leaving molecular scars that influence brain functions [324].…”
Section: Oxytocin Dysfunction As a Common Mechanism Underlying Schizo...mentioning
confidence: 99%